The Effectiveness of the Case-Based Jigsaw Model in Improving High School Students' Critical Thinking Skills on the Digestive System Topic - Anjelika Juliantari; I Made Sutajaya; I Wayan Sukra Warpala (IAIN Sorong, 2026)
Critical thinking is a key skill required in 21st-century education; however, the level of this skill among students in Indonesia remains low. This study aimed to assess the critical thinking abilities of 11th-grade students before and after the implementation of a case-based Jigsaw learning model and to compare these results with a class taught using the discovery learning model, focusing on the digestive system topic. A quasi-experimental design with a pretest-posttest control group structure was employed. The participants consisted of class XI MIPA 1 as the experimental group (n = 34), receiving the case-based Jigsaw treatment, and class XI MIPA 2 as the control group (n = 29), receiving the discovery learning treatment. Data were collected using ten essay questions covering six critical thinking indicators and analyzed using an Independent Sample t-test and Cohen’s d effect size. The results showed a significant increase in the experimental group's mean score to 84.71 (n-gain 0.70; medium category), whereas the control group's mean score rose only to 55.52 (n-gain 0.14; low category). The difference test yielded t = 22.360 (p = 0.0001 < 0.05) and a Cohen’s d of 5.65 (≥0.80, indicating a large effect). It is concluded that the case-based Jigsaw model is more effective than discovery learning in enhancing students' critical thinking skills regarding the digestive system.